2018
DOI: 10.3126/nmcj.v20i4.25142
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Pattern of Enterococcus Species Isolated from Various Clinical Specimens in a Tertiary Care Hospital, Kathmandu, Nepal

Abstract: Resistance to vancomycin and high level aminoglycosides are common among Enterococcus spp. and are being increasingly reported from different parts of the world. These resistance phenomena in enterococci have limited the therapeutic options to treat the infections caused by them. The objective of our study was to determine the antimicrobial resistance patterns of Enterococcus spp. (n=60) isolated over a year from clinical specimens received from patients visiting Nepal Medical College Teaching Hospital, Kathma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…14,23 In contrast to this study, higher prevalence of HLGR was reported in different studies from different places. 12,13,24,25 This variation may be due to varied antibiotic prescribing manner and infection control practices in different places.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,23 In contrast to this study, higher prevalence of HLGR was reported in different studies from different places. 12,13,24,25 This variation may be due to varied antibiotic prescribing manner and infection control practices in different places.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to high level gentamicin is of utmost interest as combination therapy with beta-lactam drugs are used to treat complicated Enterococcus associated infections, which restrict the therapeutic options. 12 Vancomycin resistant Enterococci (VRE) are being reported from different places at different times. Our finding shows higher incidence of VRE as compared to studies done in India (2011) 26 , Pakistan (2013) 1 , and central Nepal (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, estos autores señalan a las muestras secreciones y sangre como la segunda y tercera fuente de este microorganismo. Resultados discrepantes han sido reportados por Adhikari y col (30) , en Nepal y Castellano y col (18) , en Venezuela, quienes reportaron un mayor número de aislamientos a partir de secreciones de piel y tejidos blandos, seguidos de orina y sangre.…”
Section: /9unclassified
“…En concordancia con los resultados de esta investigación, Pinholt y col (33) , en Dinamarca, comunicaron 1,9% de resistencia a vancomicina. Adhikari (30) , en un hospital de Nepal, no detecto enterococos resistentes, sólo 8,3% de las cepas fueron intermedias. Por otra parte, Boccella y col (34) , analizaron la susceptibilidad antimicrobiana de aislamientos de Enterococcus spp obtenidos de muestras clínicas, desde 2015-2019, en un hospital universitario de Italia e informaron 0,8% y 3,2% de resistencia a este antimicrobiano en cepas de E. faecalis y E. faecium, respectivamente.…”
Section: /9unclassified